Regional occurrence of perfluoroalkane substances in human milk for the global monitoring plan under the Stockholm Convention on Persistent Organic Pollutants during 2016–2019. (August 2021) - Fiedler, Heidelore; Sadia, Mohammad
Abstract: The human milk monitoring component of the global monitoring plan under the Stockholm Convention on Persistent Organic Pollutants was implemented from 2016 to 2019 and had 44 human milk samples from primiparae collected in 42 countries and analyzed for perfluoroalkane substances (PFAS), at the MTM Research Centre at Örebro University, Sweden. The targeted compounds were restricted to the two listed PFAS (perfluorooctane sulfonic acid, PFOS and perfluorooctane carboxylic acid, PFOA) and the one recommended PFAS (perfluorohexane sulfonic acid, PFHxS). PFOA was quantified in all 44 samples in a quite narrow range (6.20 pg/g-37.4 pg/g); PFHxS was quantifiable in only four samples (max. 111 pg/g), and PFOS in 36 samples across a wide range (<6.2 pg/g-212 pg/g). Branched PFOS isomers on average had a share of 16% of the total PFOS with a maximum of 33%. PFOS was highly correlated with PFHxS (Pearson correlation coefficient R = 0.95) and weakly but still positively with PFOA (R = 0.44). Statistical analysis (all on p<0.05) showed that PFOS and PFOA in European countries were significantly different from those in African and Latin American countries and between high-income and low-income countries. PFOA tends to have higher concentrations in wealthier countries. No correlation was found for population density. Graphical abstract: Image 1 Highlights: PFOS dominates over PFOA and PFHxS in scale. PFOA occurs in all samples but on lower and narrower scale. PFHxS rarely detected, at random regional distribution. Need for identification of branched PFOS isomers and proper quantification of PFOS as a sum.